[Cp*IrCl2]2 catalyzed formation of 2,2′-biindoles from 2-ethynylanilines - Kumaran, Elumalai (2014)
Cp*IrCl2]2 catalyzes the cyclization of 2-ethynylanilines to 2,2′-biindoles via intramolecular hydroamination. A reaction pathway has been proposed on the basis of deuterium labeling experiments and computational studies.